Dual‐functioning core@shell nanofiber strip for enhancing drinking water quality: Polysulfone/graphene oxide adsorbent core layer and polyvinylpyrrolidone/mint sacrificial shell layer. Issue 44 (30th June 2021) - Hajiali, Sepideh; Khajavi, Ramin; Kalaee, Mohammad Reza; Montazer, Majid
Abstract: Drinking water quality is considered a continuing concern of human health. Herein, for the improvement of water quality, dual functioning core‐shell (CS) nanofibers were developed by use of polysulfone (PSU)/graphene oxide (GO) as the adsorbent core layer for removing heavy metal ions and polyvinylpyrrolidone (PVP)/mint extract as the shell layer for inducing antioxidant activity to the water. Various analyses on the strip samples before and after the water treatment experiment were performed. ATR‐FTIR by appearing or disappearing chemical bonds, TEM micrographs based on the formation of shell layer around the nanofibers, FESEM according to the uniformity and diameter of nanofibers, and EDX analysis based on the elemental and mapping results, verified the core‐shell structure of nanofibers. The results of the antioxidant activity demonstrated that after the dissolution shell layer, radical scavenging capability of water was improved effectively. Thereafter, the remained core layer had a high capacity and efficiency for the adsorption of metal ions especially for CS3 with 70.9% and 58.7% efficiency for Fe(III) and Ni(II). By achieving 0.975 and 0.568 L/g partition coefficient (PC), the desired performance of CS3 (core layer: 15 wt% PSU, 0.5% GO and shell layer: 5 wt% PVP, and 2.5 wt% mint) was confirmed. Abstract :